2022
DOI: 10.1172/jci148852
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose TRX2 deficiency activates mtDNA-NLRP3 to impair thermogenesis and protect against diet-induced insulin resistance

Abstract: Brown adipose tissue (BAT), a crucial heat-generating organ, regulate whole-body energy metabolism by mediating thermogenesis. BAT inflammation is implicated in the pathogenesis of mitochondrial dysfunction and impaired thermogenesis. However, the link between BAT inflammation and systematic metabolism remains unclear. Herein, we use mice with BAT deficiency of thioredoxin-2 (TRX2), a protein that scavenges mitochondrial reactive oxygen species (ROS), to evaluate the impact of BAT inflammation on metabolism an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…Increased thermogenesis and UCP1 expression have also been linked to increased fatty acid oxidation by BAT [ 52 ], similar to what is suggested by the transcriptomic findings in the IH-exposed mice in the current study. However, it has also been shown, that thermogenesis may not necessarily be associated with improved BAT nutrient handling and insulin tolerance [ 53 ] and some metabolic function of BAT is independent of UCP1-linked thermogenesis [ 54 , 55 ]. Thus, the peripheral insulin resistance we observed in BAT under chronic IH conditions is not in line with the brown phenotype in BAT and may stem from other pathophysiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Increased thermogenesis and UCP1 expression have also been linked to increased fatty acid oxidation by BAT [ 52 ], similar to what is suggested by the transcriptomic findings in the IH-exposed mice in the current study. However, it has also been shown, that thermogenesis may not necessarily be associated with improved BAT nutrient handling and insulin tolerance [ 53 ] and some metabolic function of BAT is independent of UCP1-linked thermogenesis [ 54 , 55 ]. Thus, the peripheral insulin resistance we observed in BAT under chronic IH conditions is not in line with the brown phenotype in BAT and may stem from other pathophysiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the computer algorithm MEBOCOST combining scRNA-seq transcriptome with the Human Metabolome Database has recently shown to be a promising tool in interrogating intercellular metabolite-sensor communication in BAT ( Zheng et al, 2022 ). Furthermore, despite the relatively scant discussion on BAT immunometabolism, recent report has strikingly laid out the divergence between thermogenesis and metabolic health, where the inflamed BAT promotes systemic insulin sensitivity through enhancing glucose uptake by other metabolic organs, while protecting against lipotoxicity and DIO at the expense of its energy-burning capacity ( Huang et al, 2022 ). Additionally, there is emerging recognition on the central involvement in BAT thermogenesis, where the oestrogen receptor-expressing or heat-sensing neurons has shown to modulate BAT activity and whole-body metabolic rates ( Makwana et al, 2021 ; Ye et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 can recognize both PAMPs and danger-associated molecular patterns (DAMPs), and activate NLRP3 inflammasome, which consists of NLRP3 receptor protein, apoptosis-associated speck-like protein (ASC) and caspase-1 precursor protein (pro-caspase-1). A recent study found that mtDNA leaking into the cytoplasm activated NLRP3 inflammasome in brown adipose tissue, which is engaged in obesity-induced insulin resistance and impaired thermogenesis [ 46 ]. The double-stranded DNA receptor AIM2 also recognizes mtDNA released through BAK/BAX pores, and triggers IL-1β secretion and pyroptosis [ 47 ].…”
Section: Common Types Of Mtdna Damagementioning
confidence: 99%